(3GdefGSHGJ hGdTGNUGJ GdJMaGJs - (3cGXe eMeO Ydj TcQs ((3HNW eDdagGs)
(3ChdgG (B:s
(3GdfLa GdCTQa gPg GdeOjfI Ch GdMGVQI GdESdGejI GdYQHjI GdYJjOI, dgG ceG dcd GdMhGVQ GdESdGejI efGSHGJ OjfjI hGLJeGYjI(B...s
(3BNQgG (B:s
...(3ajUQahf ajgG GdejGg GdRGFOI hejGg GdCeWGQ aj GdHjhJ haj GdThGQY, hC(B/(3G GdSQGOjH ajMJehf ajgG ef MQGQI GdUja(B.s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdeYGQa GdYGeIs